1989
DOI: 10.1093/oxfordjournals.aje.a115135
|View full text |Cite
|
Sign up to set email alerts
|

Large Fluctuations in Body Weight During Young Adulthood and Twenty-Fwe-Year Risk of Coronary Death in Men

Abstract: The hypothesis that large fluctuations in weight during young adulthood are associated with increased risk of coronary heart disease was investigated by comparing the 25-year mortality of three groups of middle-aged men with distinctly different patterns of self-reported weight during young adulthood: 98 men who reported large gains and large losses, 133 who reported large gains and no losses, and 178 who reported no substantial change in weight. They were selected from a cohort of 2,107 men aged 40-56 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
145
3
8

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(163 citation statements)
references
References 0 publications
5
145
3
8
Order By: Relevance
“…9 Similar results were reported by Hamm et al 10 for a 25-year follow-up of a large male cohort and Lissner et al 11 in a large population-based study. Studies on Weight cycling of atheletes SE Saarni et al smaller samples and intervention studies have contradictory results about the effect of weight cycling on CVD mortality and morbidity.…”
Section: Discussionsupporting
confidence: 81%
“…9 Similar results were reported by Hamm et al 10 for a 25-year follow-up of a large male cohort and Lissner et al 11 in a large population-based study. Studies on Weight cycling of atheletes SE Saarni et al smaller samples and intervention studies have contradictory results about the effect of weight cycling on CVD mortality and morbidity.…”
Section: Discussionsupporting
confidence: 81%
“…In the case of our patients, body weight variations were attributable exclusively to voluntary dieting, as was the case in the Gothenburg Prospective Studies (Lissner et al, 1989). Recently, numerous epidemiological studies have evaluated the in¯u-ence of weight cycling on cardiovascular morbidity and mortality, showing a more signi®cant correlation with weight¯uctuation Ð rather than the body mass index Ð in both cases (Hamm et al, 1989;Lissner et al, 1991;Blair et al, 1993). A signi®cant correlation has also been documented between body-fat distribution indices like the waist-to-hip ratio and the weight¯uctuation index, pointing to the possibility of body-fat redistribution, with an increase in the amount of visceral fat, in subjects with higher degrees of weight cycling (Rodin et al, 1990;Hudgins & Hirsh, 1991).…”
Section: Blood Pressure and Weight Cycling Mt Guagnano Et Almentioning
confidence: 99%
“…This possibility is extremely signi®cant, since it is a well-established fact that prevalent visceral adipose tissue deposition represents an important direct and indirect risk factor for hemodynamic, metabolic and cardiovascular comorbidities in obesity cases (Larsson et al, 1984;Seidell et al, 1987;Sjostrom, 1990;Guagnano et al, 1994;Han et al, 1995;Lean et al, 1998). Hamm et al (1989) have suggested that the increased incidence of coronary heart disease in subjects with large weight¯uc-tuations could be explained by atherogenic alterations in lipid metabolism, which take place during body weight increases after a period of caloric restriction (Bouchard, 1991). The prospective data from the Framingham Heart Study, which are particularly useful in evaluating any correlation between¯uctuations in body weight and incidence of chronic illnesses, show that changes in body weight have a negative impact, irrespective of obesity (Lissner et al, 1991).…”
Section: Blood Pressure and Weight Cycling Mt Guagnano Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a number of adverse health effects have been hypothesized to be related to episodes of weight cycling. Several prospective, epidemiological studies relating weight cycling to mortality have been more consistently positive [15][16][17][18] . These studies found that mortality was higher for persons with unstable body weight than for persons whose body weight was relatively stable, and the studies generally concluded that weight cycling resulted from unsuccessful dieting.…”
Section: Introductionmentioning
confidence: 99%